On the theory of equilibrium magnetoelastic domain structure in easy-plane antiferromagnet - Gomonaj, E. V.; Loktev, V. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Macroscopic magnetoelastic domain structure of the defectless layered antiferromagnet of CoCl2-type with the "easy-plane" magnetic anisotropy is studied theoretically in the framework of phenomenological approach. In assumption of mobile domain walls, the finite-size effects are shown to result in the formation of a stable domain structure that changes reversibly under the action of the external magnetic field and can be treated as equilibrium. It is found that in antiferromagnets, where (in contrast to ferromagnets) long-range forces of magnetic origin are absent, the domain structure and its collective behavior are governed by elasticity. Field dependence of a domain structure, magnetostriction and low-frequency AFMR of poly- and monodomain samples are calculated, the external magnetic field being directed perpendicular to the main symmetry axis of the crystal. The results obtained are in qualitative agreement with the available experimental data.